2014
DOI: 10.1111/ctr.12407
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of pancreas transplantation outcomes based on age groupings – an update of the UNOS database

Abstract: Pancreas transplants performed in patients of increasing age demonstrate decreased patient and graft survival when compared to pancreas transplants in patients <50 yr of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
58
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 19 publications
0
58
0
2
Order By: Relevance
“…We found death‐censored pancreas and kidney graft survival to be equivalent to outcomes in younger recipients. In other solid organ transplantation, death‐censored graft survival has been noted to be equivalent in older recipients , whereas in pancreas transplantation a previous UNOS database analysis suggested that optimal graft survival is seen in those aged 40–49 years with poorer graft survival in older age groups . However, single‐centre studies have not demonstrated any difference in graft outcomes between older and younger recipients.…”
Section: Discussionmentioning
confidence: 99%
“…We found death‐censored pancreas and kidney graft survival to be equivalent to outcomes in younger recipients. In other solid organ transplantation, death‐censored graft survival has been noted to be equivalent in older recipients , whereas in pancreas transplantation a previous UNOS database analysis suggested that optimal graft survival is seen in those aged 40–49 years with poorer graft survival in older age groups . However, single‐centre studies have not demonstrated any difference in graft outcomes between older and younger recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, in 2014, Siskind et al . published an analysis of more than 20 000 pancreas transplant recipients reported to UNOS. Of these, 3440 patients were over the age of 50.…”
Section: Discussionmentioning
confidence: 99%
“…However, this exclusionary practice has been based on limited data. Some authors have described acceptable outcomes in older patients, whereas others have remained more cautious . However, the risk versus benefit ratio for procedures such as pancreas transplantation can change dramatically over time as outcomes improve and as risk factors, both modifiable and nonmodifiable, become better appreciated .…”
Section: Introductionmentioning
confidence: 99%
“…This is not the first study on the subject of pancreas transplantation in the elderly; hence, the result is even less surprising. Besides some retrospective single‐centre analyses that came to similar conclusions, a UNOS database review of 20 854 patients exists and includes 3160 patients between 50 and 59 years and 280 over 60‐year old at the time of transplantation . In this register‐based analysis, an increasing patient age correlated with a significant decrease in patient and graft survival, especially in the group aged over 60 years.…”
mentioning
confidence: 91%